Work life balance and career plans of female dentist entrepreneurs - MONICA, DR. BENITA. S.; MARY. J, MS. JACKLIN (The journal of contemporary issues in business and government, 2020)
Work-life balance is a significant constituent of a healthy workplace. Keeping up work- life balance lessens the pressure and forestalls burnout in the working environment. The objective of the study is to know the impact of work-life balance on success criteria and family issues. In spite of the fact that finding a work-life balance as a dental specialist is troublesome, it altogether impacts general satisfaction, so the significance of discovering this parity couldn’t be more important. The personal family issues and the thrive to go forward in their career is highly influenced by the kind of balance they have between job and personal life. Descriptive research is used in the study and the study is focused on 67 female dentists. Work life balance affects the personal issues faced rather than the success criteria of female dentists. Based on the results, implementations are suggested for the female dentists to overcome the challenges and acquire balanced work life.